PONDOK PESANTREN DAN PENERIMAAN PENYANDANG DISABILITAS SEBAGAI UPAYA MENCIPTAKAN KEADILAN BAGI KELOMPOK RENTAN - Mukhanif Yasin Yusup (STAI Sufyan Tsauri Majenang, 2022)
One of the community groups that have so far been different and still lacks attention is people with disabilities. As individuals who have different abilities, both physically, mentally, sensory, and intellectually, their acceptance so far is still a problems. Multi-stakeholder involvement is needed to realize this goal, Inclusive society, including in Islamic boarding schools which have a strong mass base and culture in Indonesia. This is supported by the Law on Islamic Boarding Schools. Therefore, a real condition is needed regarding disability issues that exist in Islamic Boarding Schools. Research This study was conducted by in-depth interviews with several students with visual impairments (blind), deaf disabilities, and physical disabilities. Researchers still have difficulty finding students with mental and intellectual disabilities. This research focuses on traditional Islamic boarding schools, not modern Islamic boarding schools. As additional material and study literature was carried out as a reinforcement in this study. This study found the fact that discrimination for people with disabilities start from a construction related to disability which has been considered negative. Disability in the perspective of Islam actually does not exist. The benchmark for humans in Allah view is not in their physical capacity, but rather in their physical capacity, on faith and piety. Islamic boarding school as one of the important pillars in religious education and attitude that is deeply rooted has a vital role in efforts to free people with disabilities from the discrimination. In practice, acceptance is quite good, but still weak in terms of providing facilities and infrastructure , both physical and non-physical.Keywords: Disability, Islam, Discrimination, Islamic College